Optimizing Understanding of Fraction Concepts through the CoTPS Learning Model Based on EMC2 Integration in THK: - - I Made Ardana; I Putu Wisna Ariawan (Universitas Pendidikan Ganesha, 2025)
Optimizing students’ understanding of fraction concepts remains a significant challenge in mathematics education, particularly in online learning contexts. This study aims to analyze and develop the CoTPS learning model integrating EMC2 within the THK framework, designed to enhance instructional quality and strengthen students’ conceptual understanding of fractions across online, offline, and hybrid modalities. This development study refers to the Plomp model and involves teachers, media experts, and students as research participants. Data on the model’s validity, practicality, and effectiveness were collected through questionnaires and tests, then analyzed using descriptive quantitative techniques. The findings indicate that the model demonstrates very high validity with an average score of 4.42, a practicality level of 84.44%, and a mastery level of fraction understanding reaching 76.01%. These results highlight that integrating EMC2 within the THK framework can enhance learning quality by improving interaction, emotional support, and instructional guidance. However, some students still experience difficulties in understanding fractions presented in discrete representations. The implications of this study emphasize the need for further development of digital material design and visual support to better accommodate diverse student characteristics in conceptual understanding.